Immobilization of γ‐Glutamyl Transpeptidase from Equine Kidney for the Synthesis of kokumi Compounds. Issue 1 (12th November 2019) - Bruni, Margherita; Robescu, Marina S.; Ubiali, Daniela; Marrubini, Giorgio; Vanna, Renzo; Morasso, Carlo; Benucci, Ilaria; Speranza, Giovanna; Bavaro, Teodora
Abstract: γ‐Glutamyl transpeptidase from equine kidney (ekGGT, E.C. 2.3.2.2) is an intrinsic membrane enzyme which transfers the γ‐glutamyl moiety of glutathione to amino acids and peptides, thus producing γ‐glutamyl derivatives. An immobilization study of ekGGT was carried out with the aim to develop a robust biocatalyst for the synthesis of γ‐glutamyl amino acids which are known as kokumi compounds. Heterofunctional octyl‐glyoxyl‐agarose resulted in a high immobilization yield and activity recovery (93 % and 88 %, respectively). Immobilized ekGGT retained more than 95 % activity under reaction conditions (Tris‐HCl, pH 9, 0.05 M) after 6 days, whereas the residual activity after 6 reaction cycles (18 days) was 85 %. The synthesis of γ‐glutamylmethionine catalyzed by octyl‐glyoxyl‐agarose‐ekGGT afforded the product in 42 % yield (101 mg). The immobilized ekGGT was characterized by Raman spectroscopy. The immobilization protocol developed for ekGGT could be of general applicability to membrane proteins. Abstract : Immobilized and still rocking ! We have developed a tailor‐made immobilization for ekGGT, a membrane enzyme which can be used for the synthesis of γ‐glutamyl amino acids having a great interest for food applications.